Change by design : how design thinking transforms organizations and inspires innovation. - Brown, Tim, 1954- (New York : Harper Collins, 2009)
Introduction: The Power Of Design Thinking Part I What Is Design Thinking? 1 Getting Under Your Skin, or How Design Thinking Is about More Than Style 2 Converting Need into Demand, or Putting People First 3 A Mental Matrix, or "These People Have No Process!" 4 Building To Think or The Power of Prototyping 5 Returning To the Surface, or The Design of Experiences 6 Spreading The Message or The Importance of Storytelling Part II Where Do We Go from Here? 7 Design Thinking Meets the Corporation, or Teaching To Fish 8 The New Social Contract or We're All in This Together 9 Design Activism, or Inspiring Solutions With global Potential 10 Designing Tomorrow-Today Ideo Project Case Studies Index
Keywords: Organizational change; Design, Industrial